Evaluation of Dietary Bovine Milk Fat Globule Membrane Supplementation on Growth, Serum Cholesterol and Lipoproteins, and Neurodevelopment in the Young Pig - Joanne E. Fil; Joanne E. Fil; Stephen A. Fleming; Stephen A. Fleming; Maciej Chichlowski; Gabriele Gross; Brian M. Berg; Ryan N. Dilger; Ryan N. Dilger; Ryan N. Dilger; Ryan N. Dilger (Frontiers Media S.A., 2019)
Introduction: Milk fat globule membrane (MFGM) is a protein- and phospholipid-rich membrane that surrounds the lipid droplet in milk. We have previously reported that a diet composed of a combination of prebiotics, bovine MFGM (bMFGM), and lactoferrin (bLf) supported brain development in young pigs. Due to the growing interest of its potential benefits in neurodevelopment, the present study focused on the effects of dietary bMFGM alone using the pig as a translational model.Methods: Male pigs were provided ad libitum access to milk replacer with added whey protein-lipid concentrate (source of bMFGM) at 0 (CONT), 2.5 (MFGM-2.5), or 5 (MFGM-5.0) g/L from postnatal day (PND) 2 to 31. Blood was collected from pigs at PND 15 and 31, and pigs underwent behavioral testing using the novel object recognition task starting at PND 25. At PND 31, magnetic resonance imaging was conducted and animals were subsequently euthanized for tissue collection.Results: No group differences in body weight gain or milk intake were observed. At PND 31, few group differences were detected in absolute and relative brain volumes, brain water diffusivity outcomes, or behavioral parameters using the novel object recognition task. Serum lipoprotein was higher in pigs receiving diets with added dietary bMFGM compared with the CONT group. Serum cholesterol and high-density lipoprotein significantly higher (all P < 0.05) in the MFGM-2.5 compared with the CONT group. However, cholesterol concentrations within the brain prefrontal cortex and hippocampus did not differ among dietary groups.Conclusion: In this pig model, dietary supplementation with bMFGM was well-tolerated and supported growth and dietary intake similar to the control formula. Added dietary bMFGM was associated with increased serum lipoprotein, but no group differences in early brain cholesterol concentrations, macrostructure, microstructure, or recognition memory pigs at 31 days of age. Further examination of longitudinal brain development and myelination in the pig, particularly at later ages/maturation, is warranted.